(untitled) (The Pretoria Student Law Review, 2021)
The drafting of the final Constitution was a deliberate act of imposing an obligation on the newly formed democratic South Africa to recognise socio-economic rights. This was an important step in the transformation process brought about due to the transformative nature of the Constitution (better known as transformative constitutionalism), in a country that had witnessed the gross violation of human rights and institutionalised discrimination that considerably led to many of its citizens living in dire poverty through social and economic exclusion. This discussion aims to explore the justifiability of these constitutionally protected rights. In doing so, an analysis of international standards will be considered in determining whether the socio-economic rights could be said to be justifiable, followed by the constitutional influence, along with other legislative sources and judicial precedents on the matter including the role propagated by the value of ubuntu.